Development of a ,Solar Pump for Lift Irrigation Purposes - Baum, V A; Badaev, A G (Annals of Arid Zone, 2016)
The paper stresses the need for developing a medium size solar pump for lift irrigation purposes for arid areas. A summary report of some of the important developments in the field of solar pump technology, such as the fabrication of the 1.5 kw solar engine (SOMOR) in 1955, the solar turbine of Tabor in 1961, the steam engine of Farber and Presscott in 1973 and the solar steam engine of Girardeir in 1973, has been given. Evidences based on actual calculations have been presented to indicate that medium size steam engines (1 kw or less), because of their very low efficiency. have no prospects for water lifting in arid areas. Large engines based on sterling cycles are also not practicable. Small engines (1 kw) using Photovoltaic cells with proper concentrators may find wider use in tbe near future. Design details of low power solar thermoelectric generators (STEGs) of 0.5 kw for water lifting purposes have been given in this paper.